Human upper-limb force capacities evaluation with robotic models for ergonomic applications: effect of elbow flexion. Issue 4 (11th March 2016) - Hernandez, Vincent; Rezzoug, Nasser; Jacquier-Bret, Julien; Gorce, Philippe
Abstract : The aim of this study was to apply models derived from the robotics field to evaluate the human upper-limb force generation capacity. Four models were compared: the force ellipsoid (FE) and force polytope (FP) based on unit joint torques and the scaled FE (SFE) and scaled FP (SFP) based on maximum isometric joint torques. The four models were assessed from four upper-limb postures with varying elbow flexion (40°, 60°, 80° and 100°) measured by an optoelectronic system and their corresponding isometric joint torques. Ten subjects were recruited. Three specific ellipsoids and polytopes parameters were compared: isotropy, principal force orientation and volume. Isotropy showed that the ellipsoids and polytopes were elongated. The angle between the two ellipsoids main axis and the two polytopes remained low but increased with the elbow flexion. The FE and FP volumes increased and those of SFE and SFP decreased with the elbow flexion. The interest and limits of such models are discussed in the framework of ergonomics and rehabilitation.